Accounting according to the Czech legislation or IFRS? Czechia case study - Krajňák, Michal (Journal of Business Economics and Management, 2024)
The article deals with the decision-making situation whether it is more advantageous for accounting entities in Czechia to keep accounting according to Czech accounting regulations or to International Financial Reporting Standards. The preparation of financial statements only in accordance with national accounting regulations may often not be sufficient. Different ways of regulating accounting in the world put pressure on accounting harmonization. International Financial Reporting Standards are the world’s primary tools for accounting harmonization. The results of the decision analysis show that it is more advantageous for accounting entities to prepare financial statements only in accordance with national accounting regulations. The main reason for the higher utility of this option is lower costs, which is the most important criterion in the decision-making process. While accounting entities confirm that the preparation of financial statements in accordance with International Financial Reporting Standards provides higher quality and comparability of accounting information, it also provides higher costs. In the article are used methods of analysis, synthesis, comparison and a selected method of multi-criteria decision making.